Real-Time Global Illumination in Web-Browsers - Bertilsson, Marcus; Hesslow, Daniel; Jonsson, Niklas; Moos, Simon; Persson, Olle; von Essen, Hannes (My University, 2018)
Global illumination is important for a rendered image to appear realistic. Accurate global illumination can be achieved but most algorithms are very computationally expensive and only suitable for offline rendering where long rendering times can be allowed, and not for real-time rendering where many images every second is needed. We have looked at the limited case of global illumination for certain real-time applications in web-browsers. We present a comparative study of three academic papers that describe algorithms that might be suitable and successfully implemented and adapted them to our context. The results vary in terms of real-time performance, precomputation time and visual fidelity. One algorithm produced results that are not very accurate compared to a reference image but might be visually convincing enough while having the advantage of very high performance and no precomputation. The other two algorithms both produce results of higher fidelity but are generally slower in real-time and require some precomputation. One algorithm requires a couple of seconds at most and the other minutes or even hours depending on the scene. Finally, we conclude that all three techniques are suitable for rendering real-time global illumination, but they have different pros and cons.
Keywords: Data- och informationsvetenskap; Computer and Information Science